An Explanatory Study on Goods and Services Tax (GST) Compliance in Malaysia: Price, Government Subsidies, and Income Inequality - Sim, Choon Ling; Azuddin, Bahari; Abdullah, Osman; Hanum, Hassan; Yi, Jin Lim; Sin, Kit Yeng; Muhammad, Safizal (American Scientific Publishers, 2016)
Social preference in taxation policies are hard to understand and with the understanding of what people desire will help to justify public dissatisfaction thus heading towards the direction of gaining public support in the future. The purpose of this research is to explore the correlation between price, government subsidies and income inequality on GST compliance. 400 sets of questionnaires were administered in Penang state with response rate of 89% acquired via convenience sampling. The data collected were analyzed using SPSS to perform reliability, regression and correlation analysis. The findings revealed that all the selected variables have significant relationship with GST compliance.